Terahertz monolithic integrated narrow-band filter based on the silicon carbide substrate. (1st March 2023) - Liu, Yuchen; Yang, Lin-An; Li, Yang; Liu, Siyu; Chen, Yao; Zhang, Xiaoyu; Ma, Xiaohua; Hao, Yue
Abstract: This paper presented a narrow-band terahertz integrated cavity filter based on the silicon carbide (SiC) substrate. By introducing two metalized via-holes in a rectangular integrated cavity, an integrated coupling cavity was built, on the one hand, to operate as a coupling structure; on the other hand, to control the direct coupling between input and output feeding lines, further to control the frequency of the transmission zero. This novel approach was thoroughly investigated with attention paid to the position of the via-holes. Based on this approach, a terahertz narrow-band filter was realized on the semi-insulating SiC substrate, demonstrated good filtering performance, especially the stopband rejection characteristic, and established the groundwork for the production of the terahertz monolithic integrated circuit.